Neuroprotective Effect of Pseudoginsenoside-F11 on a Rat Model of Parkinson's Disease Induced by 6-Hydroxydopamine. (10th December 2013) - Wang, Jian Yu; Yang, Jing Yu; Wang, Fang; Fu, Shi Yuan; Hou, Yue; Jiang, Bo; Ma, Jie; Song, Cui; Wu, Chun Fu
Abstract : Pseudoginsenoside-F11 (PF11), a component of Panax quinquefolism (American ginseng), plays a lot of beneficial effects on disorders of central nervous system. In this paper, the neuroprotective effect of PF11 on Parkinson's disease (PD) and the possible mechanism were investigated in a rat PD model. PF11 was orally administered at 3, 6, and 12 mg/kg once daily for a period of 2 weeks before and 1 week after the unilateral lesion of left medial forebrain bundle (MFB) induced by 6-hydroxydopamine (6-OHDA). The results showed that PF11 markedly improved the locomotor, motor balance, coordination, and apomorphine-induced rotations in 6-OHDA-lesioned rats. The expression of tyrosine hydroxylase (TH) in substantia nigra (SN) and the content of extracellular dopamine (DA) in striatum were also significantly increased after PF11 treatment. Moreover, significant reduction in the levels of striatal extracellular hydroxyl radical ( ∙ OH), detected as 2, 3- and 2, 5-dihydroxy benzoic acid (2, 3- and 2, 5-DHBA), and increase in the level of striatal extracellular ascorbic acid (AA) were observed in the PF11-treated groups compared with 6-OHDA-lesioned rats. Taken together, we propose that PF11 has potent anti-Parkinson property possibly through inhibiting free radical formation and stimulating endogenous antioxidant release.